2012
DOI: 10.2169/internalmedicine.51.6962
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine Hypersensitivity Presenting as Cardiogenic Shock and Sweet's Syndrome in a Patient with Microscopic Polyangiitis

Abstract: Azathioprine hypersensitivity is a clinical syndrome which may manifest from isolated fever and rash to multi-organ failure. This rare condition is usually self-limiting following the discontinuation of azathioprine. Therefore, it is important to maintain a high index of clinical suspicion for hypersensitivity reactions with azathioprine therapy. We report a case of azathioprine hypersensitivity in a 69-year-old woman who developed cardiogenic shock and Sweet's syndrome following the initiation of azathioprine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Davis et al ., cited in [ 28 ], have suggested that imidazole moiety of AZT causes the allergic symptoms and the 6-mercaptopurine moiety the liver injury. Reintroduction of AZT should be avoided as this may lead to more serious reactions within hours of the re-challenge [ 30 ]. In summary, increased PCT may be induced by AZT-associated hypersensitivity and complicates the differential diagnosis of AAV flare versus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Davis et al ., cited in [ 28 ], have suggested that imidazole moiety of AZT causes the allergic symptoms and the 6-mercaptopurine moiety the liver injury. Reintroduction of AZT should be avoided as this may lead to more serious reactions within hours of the re-challenge [ 30 ]. In summary, increased PCT may be induced by AZT-associated hypersensitivity and complicates the differential diagnosis of AAV flare versus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Azathioprine (AZA) still corresponds to the mainstay maintenance therapy in anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitides (1,2). This drug is mostly well-tolerated, but numerous side effects are recognized.…”
Section: Introductionmentioning
confidence: 99%
“…This drug is mostly well-tolerated, but numerous side effects are recognized. These can be divided in two categories: dose-dependent toxic side effects and rarer dose-independent hypersensitivity reactions (1,3). The time lag to symptoms in hypersensitivity reactions is wide, ranging from 1 week to 16 months after starting therapy, but occurs more frequently in the first 4 weeks (1,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Most adverse effects of azathioprine, such as myelosuppression and hepatotoxicity, 2 are dose-dependent and related to drug metabolism. Azathioprine-induced Sweet's syndrome (AISS), as described in our case series, is an idiosyncratic hypersensitivity reaction, representing only 2% of the adverse effects caused by azathioprine.…”
Section: Introductionmentioning
confidence: 99%